A Comprehensive Analysis of Integrating TikTok for Enhancing EFL Students’ Speaking Skills - Asyrofi, Shiddiq; Wati, Ning Setio (Faculty of Education Universitas Nahdlatul Ulama Yogyakarta, 2024)
Mastering speaking skills is crucial for students to effectively communicate and access necessary information. Effective communication is a fundamental aspect of education and life in general, enabling individuals to express themselves clearly, engage in meaningful interactions, and convey information accurately. The research aims to investigate why TikTok is chosen as a medium for teaching speaking and assess its impact on student's speaking abilities. We conducted qualitative research. Thematic analysis was used in this research. Eight participants were involved in the study. In collecting the data, semi-structured was employed. The present study found three main findings. The first is the desire to use TikTok as media in learning English speaking. The second is a realization of using TikTok as media in learning English speaking. Thirdly, the positive impact of using TikTok to enhance their confidence in learning English speaking. Therefore, students exhibited increased confidence and comfort in expressing themselves through the application. The enjoyable nature of TikTok, coupled with its popularity among young people, contributes to its effectiveness as an innovative tool for teaching speaking skills. A suggestive suggestion for further study is the applicability of similar social media tools in language education across diverse contexts and student populations. Understanding how different groups respond to such tools can provide a more comprehensive understanding of their effectiveness. ___________________________________________________________________________________________ Menguasai keterampilan berbicara sangat penting bagi siswa untuk berkomunikasi secara efektif dan mengakses informasi yang diperlukan. Komunikasi yang efektif merupakan aspek mendasar dalam pendidikan dan kehidupan secara umum, yang memungkinkan individu mengekspresikan diri dengan jelas, terlibat dalam interaksi yang bermakna, dan menyampaikan informasi secara akurat. Penelitian ini bertujuan untuk menyelidiki mengapa TikTok dipilih sebagai media pengajaran berbicara dan menilai dampaknya terhadap kemampuan berbicara siswa. Kami melakukan penelitian kualitatif. Analisis tematik digunakan dalam penelitian ini. Delapan peserta dilibatkan dalam penelitian ini. Dalam pengumpulan data digunakan metode semi terstruktur. Penelitian ini menemukan tiga temuan utama. Yang pertama adalah keinginan untuk menggunakan TikTok sebagai media dalam belajar berbicara bahasa Inggris. Yang kedua adalah realisasi penggunaan TikTok sebagai media dalam pembelajaran berbicara bahasa Inggris. Ketiga, dampak positif penggunaan TikTok untuk meningkatkan kepercayaan diri mereka dalam belajar berbicara bahasa Inggris. Oleh karena itu, siswa menunjukkan peningkatan kepercayaan diri dan kenyamanan dalam mengekspresikan diri melalui aplikasi. Sifat TikTok yang menyenangkan, ditambah dengan popularitasnya di kalangan anak muda, berkontribusi terhadap efektivitasnya sebagai alat inovatif untuk mengajarkan keterampilan berbicara. Saran yang disarankan untuk penelitian lebih lanjut adalah penerapan alat media sosial serupa dalam pendidikan bahasa di beragam konteks dan populasi siswa. Memahami bagaimana berbagai kelompok merespons alat-alat tersebut dapat memberikan pemahaman yang lebih komprehensif tentang efektivitas alat-alat tersebut.